All Days 2000
DOI: 10.2118/62977-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Formation Imaging and Resistivity Logging in Oil-Based Drilling Fluids-Today’s Reality

Abstract: Historically, acquiring borehole image logs and resistivity at the bit measurements of useable resolution have been difficult, if not impossible, when using oil-based drilling fluids. Conversely, in many applications, drilling objectives and other performance criteria prohibit the use of water-based fluids, which deliver logs of higher resolution. Azimuthal borehole images in oil-based mud systems are delivered by wireline conveyed ultrasonic measurements or azimuthal density measurements mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For oil-in-water emulsion, it has been shown that the oil droplets were surrounded by electrolyte solution resulting in an ionic-double-layer polarization phenomenon at the fluid-tofluid interface (Lu and Yu 2002). Oil-based muds are less conductive, the nonconductive oil being the continuous phase of the emulsion (Laasted et al 2000). Above the percolation threshold of the water phase, the conductivity decreases linearly with decreasing water volume fraction.…”
Section: Electrical Properties Of Oil-based Mudsmentioning
confidence: 99%
See 1 more Smart Citation
“…For oil-in-water emulsion, it has been shown that the oil droplets were surrounded by electrolyte solution resulting in an ionic-double-layer polarization phenomenon at the fluid-tofluid interface (Lu and Yu 2002). Oil-based muds are less conductive, the nonconductive oil being the continuous phase of the emulsion (Laasted et al 2000). Above the percolation threshold of the water phase, the conductivity decreases linearly with decreasing water volume fraction.…”
Section: Electrical Properties Of Oil-based Mudsmentioning
confidence: 99%
“…Giustini et al (1996) analyzed the conductivity of water-in-oil microemulsions for a large range of water-volume fraction. Laasted et al (2000) analyzed the resistivity of oilbased mud in the range from 0.1 to 100 kHz. Below the percolation threshold, the conductivity of water-in-oil microemulsion decreases with decreasing surfactant concentration.…”
Section: Electrical Properties Of Oil-based Mudsmentioning
confidence: 99%